A Case Study of English Affricate Consonants Realized by a Two-year-old Indonesian Child - Alwasilah, Autumn; Indrayani, Lia Maulia; Soemantri, Ypsi Soeria (e-Journal of Linguistics; Vol 14 No 2 (2020): e-jl JulyDO - 10.24843/e-jl.2020.v14.i02.p03, 2020)
In English, the two affricate consonants are not owned by other languages. They are [d?] a voiced affricate like in the word jaguar, garage, and jeep, and [t?] a voiceless affricate like in the word chin, cheap, and check. These sounds are phonetic sequences consisting of a stop with a fricated release. For some EFL learners, especially children, producing those sounds are difficult because they don’t have a similar or same sound in their first or mother language like in Indonesian language. This study is aimed to explore the realization of English two affricate consonants produced by a two-year-old Indonesian child who speaks both English and Indonesian language. This qualitative case study shows a significant result on the voiced and voiceless post-alveolar consonant. The child couldn’t produce [d?] as in GA production in an initial sound of the word. She produced [j] sound instead, but she could pronounce it if the sound is in the final sound of the word. In contrast, she could pronounce [t?] as in GA production in both the initial and final sound of the word with ease. This study contributes helping English teachers to teach their students, especially children in their golden age, to pronounce English words and to contribute to the field of phonetics and phonology, specifically in teaching English pronunciations to EFL learners.